The Designer's Guide to Product Vision : Learn to build your strategic influence to shape the future - Fish, Laura; Kiekbusch, Scott (New Riders, 2020)
Today, design is a critical business competency, and designers need to play a leadership role. This guide helps you transform yourself into a strategic designer and take your seat at the table where key decisions are made. Youll master a breakthrough process for creating innovative product and service visions and translating them into high-value market offerings. Defining an effective product vision requires deep discipline and multiple skills. Drawing on their pioneering experience, Laura Fish and Scott Kiekbusch guide you through every step, helping you organize strategy, plan for innovation, and tell a clear story of your customers future experience. Once youve defined a strategy-led product vision, make it real. The authors agile Visioneering techniques help you navigate fast-changing product journeys iteratively and continuously improving experiences while staying aligned with your mission and purpose. With these tools and insights, you can lead business-critical projects today, shape your companys future, and achieve more than you ever thought possible. Learn How To: Move from tactical to strategic designer, and gain a more influential leadership role Create strategy-led product visions the organization can rally around and deliver Lead the unification of design, engineering, and business to mindfully craft outstanding user experiences Go beyond obsolete roadmaps to implement product visions in a world that wont stop changing Influence and improve the long-term direction of your business to effect real-world positive change.